Research on Accelerate the Construction of the Yellow Sea Urban Belt - Chen, Hongquan (International Journal of Social Sciences and Public Administration, 2025)
Promoting high-quality development in coastal areas and building desirable ecological and scenic belts, coastal urban belts, and high-quality economic belts are major development tasks for Jiangsu Province during the 14th Five Year Plan period. The Yellow Sea urban belt is an important node in the national "two horizontal and three vertical" urbanization pattern, an important support for the Yangtze River Delta urban agglomeration, and an important battlefield for coastal development in Jiangsu. The path and countermeasures for the construction of the Yellow Sea urban belt are: (1) Highlighting the positioning of coastal central cities, constructing a "one body, two wings" T-shaped urban spatial development pattern, and enhancing the primacy of central cities. (2) Promote the integration of people, industry, and city, enhance the industrial and population support of parks and ports, and promote the integration of coastal industrial belts and urban belts. (3) Optimize the urban system, build a "one core, one belt, and multiple nodes" spatial system, and establish a "one city, one port" county-level dual center. (4) Accelerate infrastructure construction, enhance transportation accessibility along the Yellow Sea urban belt, build a number of port cities, fishing villages, cultural and tourism towns, and characteristic villages, enhance the coastal style of the Yellow Sea urban belt, and create the "most beautiful" coast in Jiangsu.